Bibliometric Analysis of Public Sector Innovation - I Putu Yoga Bumi Pradana; Ely Susanto; Wahyudi Kumorotomo (Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This article systematically reviewed the academic research surrounding public sector innovation (PSI) to deliver an overview of PSI development in public administration (PA). This study analyzed 289 articles published between 1970 and 2020 using a bibliometric meta-analysis with HistCite software and a qualitative approach. This study found four primary research streams in PSI literature: (1) nature of public sector innovation; (2) strategy and innovation capacity; (3) adoption and diffusion of innovation; and (4) implementation and impact of innovation. Our analysis also revealed that the strategy and innovation capacity cluster has the fastest growth in publications. While the nature of the PSI stream is the least published research area, leadership, and organizational culture were the highest frequent antecedent and identified impacts in the empirical PSI studies. Finally, we offer 20 future research directions for these four research streams. This study may be the first to use HistCite bibliometric and qualitative analysis to make detailed information about each research stream of PSI literature in the PA discipline by measuring the number of publications over 50 years. The results of our review are limited to PSI publications in the PA field, which stemmed from the web of science database.